To Compare Outcome of Open Versus Laproscopic Repair for Primary Ventral Hernias - Sahibzada Saifullah Khalid, Bahrul Amin, Ahmad Arsalan Tahir, Asad Ullah Khan, Muhammad Mustafa, Muhammad Alam (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Primary ventral and incisional abdominal wall hernias are frequent conditions that necessitate surgery, and both types of hernias can be treated utilizing an open or laparoscopic technique. Improvements in laparoscopy have also been linked to a decrease in pain scores. Methodology: A dual setting study was conducted from July 2017 to June 2019 at Peshawar medical college with collaboration of Lady Reading Hospital and Hayatabd Medical Complex, Peshawar and was conducted on a total of 120 patients who were diagnosed with ventral hernia. A random number table created by a computer indicated repair of an open ventral hernia technique (group 1, n = 60) or laparoscopy (group 2, n = 60). Results: Among 60 patients in the laparoscopy group, there were 37 cases of PUH, 15 cases of epigastric hernia, 8 cases of umbilical hernia, and among 60 cases of open abdominal hernia, including 31 cases of PUH, 19 cases of hernia in the abdomen. upper abdomen, and 10 cases of umbilical hernia. Wound-related complications were most commonly seen in the open procedure group of patients. Conclusion: This has led to broad acceptance of the laparoscopic surgery, and advantages particularly in order to decrease the post-operative mortality and morbidity, time of operation, bleeding and the duration of hospital stay along the ability to execute the surgery on the obese people and with abdominal scarred individuals. Keywords: Incisional hernia, Laparoscopic mesh repair, Open mesh repair, Primary ventral hernia.